Chronic idiopathic systemic capillary leak syndrome: a case report - Alkhunaizi, Ahmed M. (Allergy Asthma Clin Immunol, 2019)
BACKGROUND: Idiopathic systemic capillary leak syndrome (ISCLS), is a rare disorder characterized by recurrent attacks of varying severity of hypovolemic shock and generalized edema in association with hemoconcentration and hypoalbuminemia in the absence of albuminuria. The chronic form of ISCLS is extremely rare with only a few cases reported in the literature. CASE PRESENTATION: Here we report the case of a young woman who developed chronic ISCLS characterized by massive, generalized and persistent edema. The work up confirmed the presence of monoclonal gammopathy. She was treated with several agents with no response. CONCLUSION: Chronic ISCLS is a very rare disease of unknown etiology and results in devastating complications. The medical community should be aware of this disease with the hope that targeted therapy will become available in the future.